2013
DOI: 10.1167/iovs.13-11902
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Intersubject Variability in Ocular Anatomical Variables on the Mapping of Retinal Locations to the Retinal Nerve Fiber Layer and Optic Nerve Head

Abstract: Mapping of retinal locations to the optic nerve head varies between patients according to a given patient's ocular parameters. By considering these parameters, patient-tailored, structure-function maps can be built and structural and functional measurements can be correlated more accurately. Individualized maps may assist clinicians detecting glaucoma and monitoring glaucomatous progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 34 publications
(41 reference statements)
3
64
0
Order By: Relevance
“…Our findings concerning the overall variability and the influence of refraction and ONH inclination on the RNFB trajectories agreed well with other studies 1,8,10 and have been discussed in detail before. 6,7 To the best of our knowledge, the significant influence of the retinal blood vessel topography on the RNFB trajectories has not been addressed before.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings concerning the overall variability and the influence of refraction and ONH inclination on the RNFB trajectories agreed well with other studies 1,8,10 and have been discussed in detail before. 6,7 To the best of our knowledge, the significant influence of the retinal blood vessel topography on the RNFB trajectories has not been addressed before.…”
Section: Discussionsupporting
confidence: 92%
“…8,9 The influence of anatomical variables including refraction, axial length, optic disc position, and optic disc dimensions on the RNFB trajectories has been studied as well. 7,8,10 Although significant factors were identified, the sources of the variability of the RNFB trajectories are not fully understood.It has been reported that the vascular and neuronal systems share many similarities. The blood vessels and nerves tend to develop in relative proximity, throughout the body of any species in general and in the primate retina in particular.…”
mentioning
confidence: 99%
“…Third, there are many factors which affect the trajectories of the retinal artery (e.g., the size, shape, and torsion of the eye). 24,25 The effect of the eye torsion was minimized by using a second-degree polynomial approach and by using the fovea-optic disc axis as a vertical landmark in measuring the retinal artery trajectory and NFLD angles. In addition, the magnification effect should not have altered angular measurements and trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that several ocular parameters may have significant influence on the layout of the RNFL. 27 Although many of those parameters are currently not available for our study, it would be possible to include information on an individual eye's distance and angle between fovea and ONH into the model we used. Another factor to consider when comparing structural and functional measurements near the fovea is the displacement of ganglion cells.…”
Section: Discussionmentioning
confidence: 99%